Pelatihan pemanfaatan Sains dan Teknologi dalam Meningkatkan Sumber Daya Manusia Masyarakat Desa Sibio-Bio - Ferawati Artauli Hasibuan; Henry Dinus Hutabarat; Nursiah Hasibuan (Yayasan Kajian Riset dan Pengembangan RADISI, 2021)
Currently the development of science and technology is very rapid in supporting human activities both in the fields of industry, agriculture, education, health, and so on. The people of Sibiobio village who tend to farm and are still lacking in utilizing the development of science and technology, especially in the fields of agriculture and education, need training activities. Given the importance of the role of science and technology in improving the welfare of the community, one of the goals of this community service is to improve human resources in the village. This service activity is carried out by conducting a survey first to find out the main problems in the area. Then an agreement was made on the time of the activity, and the main targets in the implementation of this training activity were Naposo nauli Bulung (NNB) and several village and community officials. Training activities are carried out by providing material with powerpoints, carrying out demonstrations, as well as direct practice or training to participants. Indicators of success in this training activity are the participants' responses to the activities, participants' understanding of the material and the use of science and technology, behavior change, and improvement in organization. Based on the evaluation, it was concluded that the participant's response was very high and it was hoped that there would be activities again with different topics. The participants became more aware of how to use it and some NNBs were able to develop science and technology to support their daily activities. Based on this, indirectly also changing the behavior of the participants and changing a monotonous organization to be useful with many activities to be carried out.